Coconut Plantation, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2009)
A picture of large piles of coconuts among the tall trees of a plantation.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coconut palm--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Plantations--Trinidad and Tobago; Coconut--Trinidad and Tobago